CD44 and Its Role in Solid Cancers – A Review: From Tumor Progression to Prognosis and Targeted Therapy - João Martins Gama; Rui Caetano Oliveira (Frontiers in Bioscience-Landmark)
Cluster of differentiation 44 (CD44) is a transmembrane protein expressed in normal cells but overexpressed in several types of cancer. CD44 plays a major role in tumor progression, both locally and systemically, by direct interaction with the extracellular matrix, inducing tissue remodeling, activation of different cellular pathways, such as Akt or mechanistic target of rapamycin (mTOR), and stimulation of angiogenesis. As a prognostic marker, CD44 has been identified as a major player in cancer stem cells (CSCs). CSCs with a CD44 phenotype are associated with chemoresistance, alone or in combination with other CSC markers, such as CD24 or aldehyde dehydrogenase 1 (ALDH1), and may be used for patient stratification. In the therapy setting, CD44 has been explored as a viable target, directly or indirectly. It has revealed promising potential, paving the way for its future use in the clinical setting. Immunohistochemistry effectively detects CD44 overexpression, enabling patients to be accurately selected for surgery and targeted anti-CD44 therapies. In this review, we highlight the properties of CD44, its expression in normal and tumoral tissues through immunohistochemistry and potential treatment options. We also discuss the clinical significance of this marker and its added value in therapeutic decision-making.